FRI0093 A study of incidence, risk factors and economic burden of osteoporotic fracture in rheumatoid arthritis (RA): results from two uk inception cohorts. (23rd January 2014) - Nikiphorou, E.; Carpenter, L.; Dixey, J.; Williams, P.; Kiely, P.; Walsh, D.; Williams, R.; Young, A.
Abstract : Background: Osteoporotic fracture is a recognised complication of RA, and hip fracture is a considerable economic burden for health services. Objectives: To examine the incidence rates and economic burden of, and risk factors for osteoporotic fracture in patients with RA in two UK inception cohorts. Methods: 1465 DMARD naïve patients were recruited into the Early RA Study (ERAS, 9 centres) from 1986-1998 and 1236 patients into the similarly designed early RA Network (ERAN, 23 centres) from 2002-2012. Standard clinical, radiological and laboratory measures were performed yearly for a maximum 25 and 10yrs (median 10 & 3yrs respectively). Major co morbidities and in-patient hospital episodes were recorded yearly, including fracture sites and orthopaedic interventions (OPCS codes). Clinical databases were supplemented and validated with national databases: the National Joint Registry (data available from 2003-2011), Hospital Episode Statistics (data 1997-2011), and the National Death Register (data 1986-2011). Only patients who moved abroad or were not registered with a general practitioner would be absent from national databases. Treatment regimens followed guidelines of the era, mainly conventional DMARD therapies, +/- steroids, and latterly biologics. Results: 182 fractures (#) were recorded in 176 (6.5%) patients: hip (76, 42%), wrist (32, 17.5%), vertebral (22, 12%), others (52, 28.5%). 13 hip fractures had hip replacements, 57 dynamic hip screw surgery(DHS) and 6 conservative management. There were no immediate postoperative deaths but hip and vertebral fractures were recorded as contributory causes of death in 12 and 2 respectively. Fracture incidence rates, types of surgery and direct costs over time will be displayed graphically. The median time from baseline to hip fracture was 8yrs (IQR 5-15), with average length of stay (LoS, the main driver for indirect costs) of median 15days in 1986-1994, improving to 8days in 2005-2012, but still considerably greater than national LoS figures for all hip fractures. This equals a total cost of £421, 940/€493, 191 for 70 procedures relating to hip # based on length of stay (THR for # £90, 428/€105, 698; DHS # £331, 512/€387, 456). Fracture risk included traditional factors (age, gender) and for hip fracture also included disease severity measures in 1 st year: high rheumatoid factor (OR 1.7, 95%CI 1.1-2.9), erosions (OR 2.4, 95%CI 1.4-4.0), steroid use (OR 2.7, 95%CI 1.1-6.5), high HAQ (OR 1.7, 95%CI 1.1-2.9) & ESR (OR 1.9, 95%CI 1.1-3.1), low haemoglobin (OR 1.99, 95%CI 1.2-3.1), the latter an unusual finding. Conclusions: Osteoporotic fracture complicated RA in 6.5% over 25yrs, mainly hip fractures, and not a late complication of RA. Most required major orthopaedic interventions and health costs. Risk factors for hip fracture included disease severity measures, suggesting a greater need for more active therapies for RA control and bone protection. Acknowledgements: With acknowledgement to the clinicians and nurses of the ERAS & ERAN cohorts. Disclosure of Interest: None Declared